Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis JACQ) pada Berbagai Komposisi Media Tanam dan Konsentrasi Pupuk Daun Seprint - Erida Nurahmi; Nurhayati Nurhayati; Afilia Ulfa (Jurnal Agrista, 2010)
Oil Palm Seedling Growth on Various Planting Media Compotition and Seprint Leaves Fertilizer Concentration ABSTRACT. The objective of this experiment was to study effect of various planting media compotition and Seprint leaves fertilizer concentration on oil palm seedling growth. The experiment used block randomized design with factorial pattern 3 x 3 and 3 replicants. There were two factors that studied. First factor was planting media compotition (K1 = 1 : 3; K2 = 1 : 2; K3 = 1 : 1). Second factor was seprint leaves fertilizer concentrations (S1 = 2 ml/I water; S2 = 3 ml/I water; S3 = 4 ml/I water). The result showed that the best oil palm seedling growth on planting media compotition 1:3 (cow manure : soil). The best result of oil palm seedling growth was sprint leaves fertilizer concentration 2 ml/I water. There was not interaction between planting media compotition and sprint leaves fertilizer concentration on all oil palm seedling growth variables that were studied.